CORRECTION AND EVALUATION THE KNOWLEDGE OF THE ORTHOGRAPHIC NORM IN THE PRACTICAL WORK OF TEACHING - Đorđev, Ivana Đ (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
We exam what status have orthographic mistakes in correction and evaluation the essays of the high school students. We analyzed 120 notebooks, that is 350 essays from subject Serbian language and literature in Republic of Serbia. The aim was to analyze the ways of correction that teachers use in these essays. Among all we think through the importance, methodical ways and developing the ability of correction of essays. Hypothesis was that the value of the orthography became less important in practical work of teaching and it has influenced on the teaching, understanding and behaving of the students. The orthographic mistakes are not shown all, the methodology of correction of the mistakes lacks, and the evaluation of essays is not always due to the orthographic mistakes, other irrelevant things may affect it. The teachers do not check the improvement of the students and also do not check correction of essays of the students in high school. Actually the correction and evaluation of essays are superficial and automatic. In this work there are suggestions as a solution of this problem.